A synthetic methodology toward π-extended porphyrin-rylenediimide conjugates - Oleszak, Christoph; Ritterhoff, Christian; Schulze, Erik; Hirsch, Andreas; Meyer, Bernd; Jux, Norbert (RSC Advances, 2025)
In this work, we present a straightforward synthetic route for the preparation of functionalized β-meso-fused porphyrins, which are subsequently connected to rylendiimides. The resulting donor-acceptor-type conjugates exhibit intriguing optical properties, such as panchromatism and profoundly bathochromically shifted absorption curves. A better understanding of the molecules' electronic structure was gained through density-functional theory calculations, which unveiled small HOMO-LUMO gaps.
CRIS-Team Scopus Importer:2025-01-31

Regioselective Synthesis of Hamilton‐Receptor‐Fullerene Oligo‐Adducts for the Supramolecular Binding of Cyanuric Derivatives - Wachter, Michael; Scholz, Barbara; Schulze, Erik; Hampel, Frank; Perez-Ojeda Rodriguez, Maria Eugenia; Hirsch, Andreas (Chemistry - A European Journal, 2024)
A new concept for the regioselective synthesis of Hamilton-receptor and cyanurate-functionalized oligo adducts of the fullerene C60 was developed. Based on an in-situ deprotection and click-post-functionalization approach with novel azido precursors, the corresponding fullerene hexakis-adducts with octahedral addition patterns and up to twelve Hamilton-receptor/cyanurate moieties surrounding the fullerene sphere were synthesized. The versatility of this approach was further demonstrated by the synthesis of Hamilton-receptor/cyanurate functionalized fullerene mono-adducts, which are not accessible by direct cyclopropanation. Several fullerene target compounds were purified by simple washing procedures of the solid crude reaction mixture without the need for chromatography. The resulting fullerene mono- and hexakis-adducts were fully characterized and their supramolecular properties were investigated by NMR-spectroscopy and isothermal titration calorimetry (ITC).<br

Site- and Enantioselective Iridium-Catalyzed Desymmetric Mono-Hydrogenation of 1,4-Dienes - Wu, Haibo; Su, Hao; Schulze, Erik; Peters, Bram B. C.; Nolan, Mark D.; Yang, Jianping; Singh, Thishana; Ahlquist, Mårten S. G.; Andersson, Pher G. (Angewandte Chemie International Edition, 2021)
The control of site selectivity in asymmetric mono-hydrogenation of dienes or polyenes remains largely underdeveloped. Herein, we present a highly efficient desymmetrization of 1,4-dienes via iridium-catalyzed site- and enantioselective hydrogenation. This methodology demonstrates the first iridium-catalyzed hydrogenative desymmetriation of meso dienes and provides a concise approach to the installation of two vicinal stereogenic centers adjacent to an alkene. High isolated yields (up to 96 %) and excellent diastereo- and enantioselectivities (up to 99:1 d.r. and 99 % ee) were obtained for a series of divinyl carbinol and divinyl carbinamide substrates. DFT calculations reveal that an interaction between the hydroxy oxygen and the reacting hydride is responsible for the stereoselectivity of the desymmetrization of the divinyl carbinol. Based on the calculated energy profiles, a model that simulates product distribution over time was applied to show an intuitive kinetics of this process. The usefulness of the methodology was demonstrated by the synthesis of the key intermediates of natural products zaragozic acid A and (+)-invictolide.
Created from Fastlane, Scopus look-up
Keywords: 1; 4-diene; asymmetric hydrogenation; iridium catalysis; site selectivity

Synthesis and Aggregation of Amphiphilic Porphyrin-Perylenebisimide Dyads - Schulze, Erik; Wu, Mingjian; Methfessel, Christian; Spiecker, Erdmann; Hirsch, Andreas (Chemistry - A European Journal, 2025)
We report the straightforward synthesis of a family of amphiphilic zinc-porphyrin-perylenebisimide (PBI) dyads containing sterically demanding substituents at the porphyrin meso-position, as well as at the PBI bay-position. The hydrophilic head group consists of oligo-carboxylic acid G2-Newkome dendrons attached to the porphyrin, whereas lipophilic pentyl-hexyl-swallowtails are connected to the PBI imide position. Using UV/Vis absorption and fluorescence emission spectroscopy, their tetrahydrofuran (THF) initiated disaggregation was studied in aqueous media. Without meso-substituents, a stronger interaction between the porphyrins was observed in the aggregated state. Insights into the size and morphology of the aggregates were obtained by dynamic light scattering (DLS) and scanning transmission electron microscopy (STEM). Supported by density functional theory (DFT) calculations, these revealed micelles and liposomes as plausible architectures.
CRIS-Team Scopus Importer:2025-05-16
Keywords: aggregation; amphiphiles; donor-acceptor-hybrids; perylenebisimide; porphyrinoids

Synthesis and Characterization of Bola-Amphiphilic Porphyrin-Perylenebisimide Architectures - Schulze, Erik; Ritterhoff, Christian; Franz, Evanie; Tavlui, Olha; Brummel, Olaf; Meyer, Bernd; Hirsch, Andreas (Chemistry - A European Journal, 2024)
We report on the synthesis and characterization of a family of three water-soluble bola-amphiphilic zinc-porphyrin-perylenebisimide triads containing oligo carboxylic-acid capped Newkome dendrons in the periphery. Variations of the perylenebisimide (PBI) core geometry and dendron size (G1 and G2 dendrons with 3- and 9-carboxylic acid groups respectively) allow for tuning the supramolecular aggregation behavior with respect to variation of the molecular architecture. The triads show good solubility in basic aqueous media and aggregation to supramolecular assemblies. Theoretical investigations at the DFT level of theory accompanied by electrochemical measurements unravel the geometric and electronic structure of the amphiphiles. UV/Vis and fluorescence titrations with varying amounts of THF demonstrate disaggregation.
CRIS-Team Scopus Importer:2024-01-19
Keywords: Aggregation; Amphiphiles; Donor-Acceptor-Hybrids; Perylenebisimide; Porphyrinoids